Plasma Purification Treatment Relieves the Damage of Hyperlipidemia to PBMCs - Zhang, Xiao Meng; Gu, Yan Hong; Deng, Hao; Xu, Zheng Quan; Zhong, Ze Yuan; Lyu, Xia Jie; Jin, Hui Min; Yang, Xiu Hong (Frontiers in Cardiovascular Medicine, 2021)
Background: Hyperlipidemia {hypercholesterolemia [cholesterol >5.18 mmol/L) or hypertriglyceridemia [triglycerides >2.3 mmol/L], mixed hyperlipidemia [cholesterol >5.18 mmol/L and triglycerides >2.3 mmol/L], and high low-density lipoproteinemia [low-density lipoprotein (LDL) >3.4 mmol/L]} is a strong risk factor for arteriosclerosis and cardiovascular disease (CVD). Therapy with lipid-lowering drugs often results in many side effects. Our study aimed to investigate the potential effects of non-drug therapy with double-filtration plasmapheresis (DFPP) on lipid metabolism-, endoplasmic reticulum (ER) stress-, and apoptosis-related proteins in peripheral blood mononuclear cells (PBMCs) before and after lipid clearance in patients with hyperlipidemia. Methods: Thirty-five hyperlipidemia patients were selected. Proteins related to lipid metabolism [CD36, proprotein convertase subtilisin/kexin type 9 (PCSK9), and LDL receptor], ER stress [glucose-regulated protein 78 (Grp78), C/EBP homologous protein (CHOP), activating transcription factor 4 (ATF4), and eukaryotic initiation factor 2α (EIF2α)], and apoptosis [B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein (BAX), and cysteinyl aspartate specific proteinase-3 (Caspase-3)] were assayed by Western blot, reactive oxygen species (ROS) were measured by flow cytometry (FCM), and ELISA detected serum inflammatory [interleukin (IL)-1β, IL-6, and tumor necrosis factor α (TNF-α)] factors. Results: Compared with their pre-DFPP values, the values of most lipid metabolic parameters, such as cholesterol, triglycerides, LDL, lipoprotein a [Lp(a)], and small dense LDL (sdLDL) cholesterol, were reduced after DFPP. DFPP was associated with the downregulation of proteins related to lipid metabolism, ER stress, and apoptosis, resulting in decreased ROS and serum inflammatory factor release. Conclusion: DFPP has lipid-lowering activity and can also regulate lipid metabolism-, ER stress-, and apoptosis-related proteins in PBMCs and reduce the levels of inflammatory factors in patients with hyperlipidemia (ClinicalTrials.gov number: NCT03491956).